Nondestructive testing of high-performance ceramics : conference proceedings, August 25-27, 1987, Boston, MA - Joint Conference on Nondestructive Testing of High-Performance Ceramics (1987 : Boston, Mass.); Vary, Alex; Snyder, Jack (Westerville, Ohio : American Ceramic Society, 1987)
09